Excessive use of herbal teas as medicinal adjuncts among health science students from a University in Paraná, Brazil (Research, Society and Development, 2025)
Introduction: Herbal teas have been integral to various cultural practices worldwide and have been used for medicinal purposes for thousands of years. According to the World Health Organization (WHO), the use of medicinal plants or their preparations for basic health care remains common today. Nevertheless, studies emphasize the importance of understanding toxicity levels, proper preparation methods, and the importance of professional guidance rather than informal recommendations from friends or family. This is particularly relevant given the widespread perception that teas are harmless due to their natural origin. Objective:To investigate the prevalence of medicinal tea consumption among health science students at the Universidade Paranaense, Cascavel campus. Methods: This quantitative, cross-sectional study was conducted using an electronic questionnaire to assess the incidence and characteristics of herbal tea use among university students. Results: Among the 368 participants, 63.3% reported using teas for therapeutic purposes. The most commonly consumed teas were Chamomile (86.4%), Fennel (63.8%), and Lemon Balm (61.4%). The primary motivations for consumption included relief from anxiety/stress (51.9%) and improved digestion (48.9%). Reported adverse effects included nausea and polyuria. Over half of participants had never received professional guidance and reported self-directed use. Conclusion: A significant portion of the study population uses herbal teas as therapeutic alternatives without professional supervision. In most cases, users are unaware of potential adverse effects and the appropriate usage of these substances, highlighting the need for better education and regulation regarding phytotherapeutic practices.